Associations of number of teeth with risks for all‐cause mortality and cause‐specific mortality in middle‐aged and elderly men in the northern part of Japan: the Iwate‐KENCO study. Issue 4 (29th January 2014) - Ando, Ayumi; Tanno, Kozo; Ohsawa, Masaki; Onoda, Toshiyuki; Sakata, Kiyomi; Tanaka, Fumitaka; Makita, Shinji; Nakamura, Motoyuki; Omama, Shinichi; Ogasawara, Kuniaki; Ishibashi, Yasuhiro; Kuribayashi, Toru; et al.
Abstract Objectives The objective of this study was to determine the associations of number of teeth with all‐cause mortality and cause‐specific mortality among middle‐aged and elderly Japanese men. Methods A total of 7779 men aged 40–79 years who were free from cardiovascular disease (CVD) were followed up prospectively for 5.6 years. Participants were categorized into four groups (no teeth, 1–9 teeth, 10–19 teeth, and ≥20 teeth) by a self‐administered questionnaire. Using Cox's proportional hazard model, multivariate hazard ratios (HRs) and 95% confidence intervals (CIs) for mortality from all causes, CVD, cancer, and noncancer, non‐CVD according to number of teeth were estimated with adjustments for age, body mass index, systolic blood pressure, total‐ and HDL‐cholesterol, HbA1c, current smoking, current alcohol drinking, and low level of education. Results The numbers (proportions) of participants with no teeth, 1–9 teeth, 10–19 teeth, and ≥20 teeth were 1613 (20.7%), 1650 (21.2%), 1721 (22.1%), and 2795 (35.9%), respectively. During follow‐up, a total of 455 deaths (including 175 deaths from cancer, 98 deaths from CVD, and 130 deaths from noncancer, non‐CVD) were recorded. In total participants, an inverse relationship between number of teeth and all‐cause mortality was found (P for trend = 0.049). Among men aged 40–64 years, inverse relationships were also found in risks for mortality from all causes, CVD, and cancer: multivariate‐adjusted HRs (95% CI) for all‐cause mortality in men with no teeth, 1–9 teeth, and 10–19 teeth relative to men with ≥20 teeth were 2.75 (1.37–5.49), 1.89 (0.99–3.63), and 1.94 (1.09–3.43), respectively. However, there were no associations of number of teeth with all‐cause mortality and cause‐specific mortality among men aged 65–79 years. Conclusions The number of teeth is an important predictive factor for mortality among middle‐aged Japanese men.